Analisa Faktor Budaya dengan Penyembuhan Luka Perineum Post Partum di PMB Siti Salmah Tahun 2022 - Feby Monika Sari; Omega DR Tahun (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Perineal wounds are defined as tears in the birth canal or due to episotomy at the time of giving birth to the fetus.  Data from the Profile of the Jakarta Regional Health Office in 2020, there were 7,466 puerperal mothers, and an estimated 1,864 people who experienced perineal tears.Objektive: The aim of the research was to determine the influenced factors; age, hygien , culture, and family support to heal of perineal injury in mother normal postpartum. Methods: The kind of the research was explanatory survey with cross-sectional design. The population was normal mothers in postpartum (10-14 days) location at the primary health   center   Jeumpa,   Gandapura,   and   Kuta   Blang   in   Bireuen   district, and the Samples are   44 mothers. Analysis data using univariate, bivariate, and multivariate.Results: The results of the chi square statistical test showed that the variable related to perineal wound healing was Culture (p value = 0.001; OR =1.89), parity (p value = 0.005; 0R = 1.90) and variables unrelated to perineal wound healing are age (p value 0.60 ;OR = 1.10).Conclusion: There is a relationship between perineal wound healing with culture and parity. Midwives should provide education more actively for mothers in  postpartum about the importance of keeping injury in the birth canal, and the participation of her husband and family to help new mothers in the injury healing process.